Neoproterozoic evolution of the São Francisco Basin, SE Brazil : effects of tectonic inheritance on foreland sedimentation and deformation. - Reis, Humberto Luis Siqueira (2016)
Programa de Pós-Graduação em Evolução Crustal e Recursos Naturais. Departamento de Geologia, Escola de Minas, Universidade Federal de Ouro Preto.